#TITLE_ALTERNATIVE# - AIRLANGGA (NIM 12204014); Pembimbing: Dr. Ir. Sudjati Rachmat, DEA., GILANG
S-A field is one of oil field located on Papua's bird head. Reservoir was identified as naturally fractured carbonate with strong water drive mechanism. Previous reservoir modeling study has defined 50,810.85 MSTB proven reserves with 20,876 MSTB maximum recoveries. As 20,972 MSTB oil had been produced cumulatively on 2007, indicate bigger maximum recovery compared to previous model's maximum recovery. On 2008, new reservoir study has been done aiming better definition of reserve and maximum recovery from S-A field. This paper is defined as an ongoing study from previous geological modeling study done. Simulation study procedures consist of (1) geological model review, (2) data acquisition, (3) reservoir properties distribution along validated geological model, (4) model initialization based on volumetric calculated reserve, (5) history matching to production data. Throughout this study, a reservoir model defines better definition of reserve and maximum recovery of S-A field will be resulted thus production optimization of S-A field can be prepared.